2016
DOI: 10.1016/j.nmni.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of CTX-M-15-type β-lactamases in Escherichia coli strains from Senegal

Abstract: We aimed to detect the extended-spectrum β-lactamases (ESBLs) secreted by clinical strains of Escherichia coli at Fann University Hospital in Dakar and to characterize them molecularly. We identified 32 isolates producing ESBLs. The CTX-M-15 gene was the most frequently detected ESBL gene, detected in 90.63% of the isolates studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…The worldwide expansion of the community acquired ESBL gene, CTX-M [39] is thus confirmed in this study and also its association with TEM and SHV genes, previously reported in studies on E. coli from urinary specimens in Europe [40], Asia [41,42], America [43,44] [25]. The combination of ESBL genes is more common in this study 72/91, 79.12% than in Burkina Faso, with 6/96, 6.96% [24], in Senegal, 13/32, 40.63% [45] and in Morocco, 2/7, 28.57% [35].…”
Section: Discussionsupporting
confidence: 89%
“…The worldwide expansion of the community acquired ESBL gene, CTX-M [39] is thus confirmed in this study and also its association with TEM and SHV genes, previously reported in studies on E. coli from urinary specimens in Europe [40], Asia [41,42], America [43,44] [25]. The combination of ESBL genes is more common in this study 72/91, 79.12% than in Burkina Faso, with 6/96, 6.96% [24], in Senegal, 13/32, 40.63% [45] and in Morocco, 2/7, 28.57% [35].…”
Section: Discussionsupporting
confidence: 89%
“…However, molecular methods such as PCR are not readily available in the hospital setting and can only be seen in research facilities. A study by Dia et al (2015) identified 32 E. coli isolates to be ESBLs producers and blaCTX-M gene was reported to be the most frequent ESBL gene with 90.63% frequency. Similarly, Ugbo et al (2020) and Sharma et al (2010) reported 55 and 56% blaTEM frequency, respectively among E. coli of clinical origin; and this is in agreement with this present study where we reported 32.7 and 67.3% frequencies for TEM and CTX-M genes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Microbial resistance by pathogenic Escherichia coli is a major worldwide concern. Antibacterial agents, especially beta-lactams are becoming less useful against Enterobacteriaceae (Dia et al, 2015). Urinary tract infections (UTIs), a common nosocomial and communityacquired bacterial infection, occur in all genders and age groups (Abdulaziz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Illustrative map of Europe showing countries with description of E-ESBL in cattle and beta-lactamases type.2014;Dia et al, 2016;Fam et al, 2011;Hasan et al, 2016;Hern andez et al, 2012;Liao et al, 2017;Poirel et al, 2013;Ruiz et al, 2011;Sidjabat et al, 2010).…”
mentioning
confidence: 99%